2017
DOI: 10.1111/andr.12439
|View full text |Cite
|
Sign up to set email alerts
|

Naringenin attenuates highly active antiretroviral therapy‐induced spermDNAfragmentations and testicular toxicity in Sprague‐Dawley rats

Abstract: SUMMARYHighly active antiretroviral therapy has evolved over the years, leading to a boost in the quality of life in people living with HIV and AIDS. However, growing evidence has shown that highly active antiretroviral therapy has deleterious effects on the testes and the overall reproductive capacity. Therefore, this study is to determine the adjuvant potential of Naringenin on highly active antiretroviral therapy-induced perturbations in fertility of male Sprague-Dawley rats. Thirty adult male Sprague-Dawle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 91 publications
(98 reference statements)
6
24
0
Order By: Relevance
“…It is demonstrated that in stressful conditions, naringenin has the ability to chelate irons and decrease ROS production. Interestingly, it is related to the fact that naringenin has 5-hydroxy and 4-carbonyl groups in the C-ring which plays a role in ROS scavenging, Cu, and Fe ions interaction [38, 39]. Therefore, adding naringenin to the cryopreservation medium can decrease the stress caused by freezing, consequently can increase motility which was observed in our study.…”
Section: Discussionsupporting
confidence: 54%
“…It is demonstrated that in stressful conditions, naringenin has the ability to chelate irons and decrease ROS production. Interestingly, it is related to the fact that naringenin has 5-hydroxy and 4-carbonyl groups in the C-ring which plays a role in ROS scavenging, Cu, and Fe ions interaction [38, 39]. Therefore, adding naringenin to the cryopreservation medium can decrease the stress caused by freezing, consequently can increase motility which was observed in our study.…”
Section: Discussionsupporting
confidence: 54%
“…Thirty (30) disease‐free adult male SD rats were randomly divided into 6 equal number groups. Group A served as control and was given distilled water, B was given the FDC of HAART containing TDF/FTC/EFV, C had naringenin, 40 mg/kg, D had naringenin, 80 mg/kg (Adana et al, ). The last two groups, E and F had TDF/FTC/EFV and naringenin 40 and 80 mg/kg respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Sperm morphology was accessed by staining dry smeared spermatozoa on glass slide with eosin‐nigrosin staining. Morphology was described as normal, abnormal head, abnormal midpiece, and abnormal tail (Adana et al, ; Azu et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations